Penerapan Right To Be Forgotten dalam Melindungi Identitas Anak sebagai Pelaku maupun Korban pada Konten Kekerasan dan Seksual di Platform Media Sosial - Vina Yunita; Ai Permanasari (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The spread of content depicting children as perpetrators or victims of violence on social media platforms such as TikTok, Instagram, and X raises serious issues related to privacy and digital footprints. The Right to Be Forgotten (RTBF) provides children or guardians with the right to delete detrimental personal data as an effort to restore their digital identity and privacy. This study uses normative juridical methods and a conceptual approach to analyze the Indonesian legal framework of the ITE Law, the PDP Law, and the Child Protection Law and compares them with best practices in the European Union, Australia, and France. The results show that RTBF in Indonesia has a clear legal basis, but its implementation remains limited due to slow platform response, lengthy court procedures, the absence of an independent oversight body, and the rapid spread of content. This study emphasizes the need for a non-litigation deletion mechanism, a strong oversight body, and the application of the best interest of the child principle to ensure comprehensive protection of children's identities in the digital realm. With strengthened regulations and public awareness, RTBF can be an effective instrument in preventing stigmatization and supporting children's social rehabilitation.